Kolaborasi Sekolah, Orang Tua, dan Masyarakat dalam Pendidikan Islam: Systematic Literature Review - Nur Azizah; Kasful Anwar (Ikhlas : Jurnal Ilmiah Pendidikan Islam, 2026)
Islamic education requires close collaboration between schools, parents and the community; however, research on this partnership has not yet been systematically synthesised. This study aims to identify the patterns, challenges and implications of this tripartite partnership in Indonesia through a Systematic Literature Review (SLR) approach. A qualitative method based on SLR was used to analyse ten open-access academic articles published over the last 10 years from Google Scholar, Garuda and academic repositories, using a matrix synthesis. The research findings indicate that the most dominant patterns of collaboration include school–parent communication, family involvement in character building, and active community participation in supporting religious activities. Conversely, the main challenges include poor communication, low participation, differing perceptions of responsibility, and the lack of optimal mechanisms for sustainable institutional partnerships. The researchers concluded that structured and sustainable collaboration is a key pillar in enhancing the effectiveness of Islamic education in Indonesia. It is hoped that these findings will serve as an academic reference for educational institutions, parents and policymakers in developing partnership models in a more systematic manner.